Komunikasi Interkultural Dalam Membangun Harmoni Lintas Agama Antara Umat Islam, Katolik dan Khonghucu di Kampung Kerukunan Ciamis - Ayu Ariska; Farhan Denia Ramadhan; Dadan Anugrah; Acep Aripudin (IAIN Padangsidimpuan, 2026)
This study aims to analyze the intercultural communication model applied by the Muslim, Catholic, and Confucian communities in fostering interreligious harmony in kampung Kerukunan, Ciamis regency. The research employs a qualitative descriptive approach through in depth interviews with key regilious figures: Ventiko (Catholic), Asep (Muslim), and Andi Sanjaya (Confucian). Findings indicate that the communiacation patterns among different faiths in kampung Kerukunan reflect the core principles of William B. Gudykunst’s Anxiety/Uncertainty Management (AUM) Theory, emphasizing anxiety management, uncertainty reduction, and emphaty building in cross-cultural interaction. Harmonious relationships are manifested in joint social religious activities, shared worship spaces, and institutional support from the Interreligious Harmony Forum (FKUB). This study concludes that intercultural communiacation grounded in religious values and mutual respect plays a vital role in sustaining social cohesion in a multireligious society.